2022
DOI: 10.3390/inventions7010030
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Placement of Solar Power Plant and Interline Power Flow Controllers for Prevention of Blackouts

Abstract: In these post COVID times, the world is going through a massive restructuring which India can use to its benefit by attracting foreign industrial investment. The major requirement is a reliable and ecofriendly electrical power source. Of late, renewable energy sources have increasingly become popular as alternative source of electricity. They can provide immense aid in improving the reliability of the power system, when placed properly. The alternative integrated energy sources along with FACTS devices can pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…d. The centers of clusters are updated using the average of all data points of each cluster as (18):…”
Section: K-means-based Dcmmentioning
confidence: 99%
See 1 more Smart Citation
“…d. The centers of clusters are updated using the average of all data points of each cluster as (18):…”
Section: K-means-based Dcmmentioning
confidence: 99%
“…In [17], it is shown that the placement of the IPFC improves the voltage stability of the power system and the line loading capability. In [18], the optimal allocation of the IPFC and the solar power unit using the line severity index has been investigated to avoid contingencies. The allocation cost of the IPFC has been ignored in both studies, and only operational aspects are considered.…”
Section: Introductionmentioning
confidence: 99%